Visualization of fracture progression in peridynamics. (October 2017) - Bußler, Michael; Diehl, Patrick; Pflüger, Dirk; Frey, Steffen; Sadlo, Filip; Ertl, Thomas; Schweitzer, Marc Alexander
Highlights: Visualization of fracture processes in peridynamics using height ridge surface extraction on nodes without resampling. Visualization of fracture processes in peridynamics using height ridge surface extraction on nodes without resampling. Temporal stability is achieved by progressively combining ridges into a reference state over time. For analysis, we use and integrate spatiotemporal visualization of fracture progression, growth velocity, and correlation with stress. Our approach allows one to gain new insights in peridynamics simulations, i.e. extraction of crack surfaces. Here, domain scientist can achieve new insights how crack fronts grow in peridynamic simulations. Abstract: We present a novel approach for the visualization of fracture processes in peridynamics simulations. In peridynamics simulation, materials are represented by material points linked with bonds, providing complex fracture behavior. Our approach first extracts the cracks from each time step by means of height ridge extraction. To avoid deterioration of the structures, we propose an approach to extract ridges from these data without resampling. The extracted crack geometries are then combined into a spatiotemporal structure, with special focus on temporal coherence and robustness. We then show how this structure can be used for various visualization approaches to reveal fracture dynamics, with a focus on physical mechanisms. We evaluate our approach and demonstrate its utility by means of different data sets.